2016
DOI: 10.1111/jphs.12160
|View full text |Cite
|
Sign up to set email alerts
|

Trends in emergency hospital admissions in England due to adverse drug reactions: 2008-2015

Abstract: Objectives To determine the scale of adverse drug reaction (ADR)-related emergency hospital admissions in England from 2008 to 2015 using the Hospital Episode Statistics (HES) database. Methods Part of the HES database contains information about all hospital admissions in England. Annual data are published online and are publically available. These hospital admission data were analysed to determine how many emergency admissions were due to ADRs. International classification of diseases, 10th edition (ICD-10) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…This study demonstrated a significant increase of 5.8% per annum of ADR‐related hospitalisations in NSW, with the age‐adjusted incidence rate of ADR‐related hospitalisations nearly doubled over 13 years. The observed increasing pattern was consistent with previous findings in Western Australia, England, the United States and Spain . Alarmingly, study cases with severe comorbid conditions and in‐hospital deaths also increased over time, in comparison with a fairly steady trend of all‐cause in‐hospital deaths in Australia (crude rates from 346.7 per 100 000 in 2005–2006 to 328.4 in 2014–2015), reflecting an urgent need for clinical attention.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study demonstrated a significant increase of 5.8% per annum of ADR‐related hospitalisations in NSW, with the age‐adjusted incidence rate of ADR‐related hospitalisations nearly doubled over 13 years. The observed increasing pattern was consistent with previous findings in Western Australia, England, the United States and Spain . Alarmingly, study cases with severe comorbid conditions and in‐hospital deaths also increased over time, in comparison with a fairly steady trend of all‐cause in‐hospital deaths in Australia (crude rates from 346.7 per 100 000 in 2005–2006 to 328.4 in 2014–2015), reflecting an urgent need for clinical attention.…”
Section: Discussionsupporting
confidence: 88%
“…The observed increasing pattern was consistent with previous findings in Western Australia, England, the United States and Spain. 8,9,11,12 Alarmingly, study cases with severe comorbid conditions and in-hospital deaths also increased over time, in comparison with a fairly steady trend of allcause in-hospital deaths in Australia (crude rates from 346.7 per 100 000 in 2005-2006 to 328.4 in 2014-2015), 21 reflecting an urgent need for clinical attention. A previous study has reported that more than half of ADR-related hospitalisations could be prevented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of MRH in older adults found that between 17% to 51% of older adults experience MRH within 30 days of hospital discharge . In England, MRH is leading to an increasing number of hospital admissions . The direct health care costs of MRH in older adults following hospital discharge in England is conservatively estimated at £400 million annually, of which 90% of cost is attributable to hospital readmission …”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug reactions (ADRs) are associated with significant morbidity and mortality worldwide [1]. A study conducted to determine the number of ADR-related emergency hospital admissions in England reported an increase in ADR-led admissions from 1.2% in 2008 to 1.6% in 2015 [2]. In Saudi Arabia, the frequency of ADR-related hospital admissions was reported to be 6.1 per 100 admissions and 7.9 per 1000 patient days [3].…”
Section: Introductionmentioning
confidence: 99%